Social Vulnerability A qualitative research on the reasons behind social vulnerability in Erbil city - Mohammed Azeez, Muzhda (Zanco Journal of Human Sciences, 2023)
The term "social vulnerability" is not frequently used to describe people or communities in Erbil. It is a new term that is common.y used in social sciences for academic purposes. The term "social vulnerability" refers to an individual or a community that has weaknesses in their security, economy, and social aspects that make them unable to face a disaster, whether natural or man-made, and come out with little loss. following the disaster, these vulnerable people have limited ability to rebuild. The researcher has noticed that after COVID-19, there were an increase number of vulnerable people in Iraq - KRI included. According to reports published by USAID 2021 and UNICEF 2020 on vulnerability of Iraqi people following the pandemic found that poverty "economy" a major factor contributing to the high level of vulnerability in Iraq. Erbil city has been included in their data as a part of KRI, and the rate of vulnerability due to poverty has been increased "Kurdistan region, again, would experience highest increase in near poverty rate" (UNICEF, 2020, p. 11).